Stability of anthocyanins from rubus glaucus and solanum betaceum as affected by temperature and water activity (2009)
The stability of sprayed-dried microencapsulated anthocyanins from Andes berry (Rubus glaucus) and Tamarillo (Solanum betaceum), as affected by storage time, water activity (Aw) and temperature was compared. The fruits were osmotically dehydrated with ethanol and the anthocyanin extract was microencapsulated with maltodextrin DE 20 by spray drying. Half life of the anthocyanins; changes in color, total phenolics, and antioxidant activity of the powders, were analyzed during storage at two different temperatures (25 °C and 40 °C) and two Aw levels (0.20 and 0.35). A decrease in monomeric anthocyanin was observed in both samples. The half life of the Andes berry pigments ranged between 11 and 32 days while the half life of the tamarillo pigments ranged between 9 and 21 days. A darkening effect occurred in both samples as a result of storage time.  The antioxidant activity decreased while the phenolic content increased with time. Antioxidant activity of Andes berry samples was highly correlated with anthocyanin content and total phenolic content while the antioxidant activity of tamarillo samples was highly correlated with total phenolic content. These results would be useful in developing applications for spray-dried anthocyanin as powdered food-grade colorants.